Development of a Modular Retrofitting System for Residential Buildings and Experience from Pilot Installation. (June 2019) - Hejtmánek, P; Sojková, K; Volf, M; Lupíšek, A
Abstract: In order to significantly reduce energy consumption of its building stock, Europe has to focus on energy retrofitting of existing buildings. A usual building retrofitting process is very labour intensive and time consuming. It usually takes several weeks or even months to replace old windows by new, install new thermal insulation layers on the external walls and roofs of buildings and renew the heat distribution systems or to attach renewable energy sources on the building's envelope. To make refurbishment more efficient and allow its scaling up, a European project Development and Advanced Prefabrication of Innovative, Multifunctional Building Envelope Elements for Modular Retrofitting and Connections (MORE-CONNECT) has been initiated under H2020 program. This project developed a system of prefabricated retrofitting modules, that enable to cut primary energy consumption of a typical residential building by 80 %, reduce on-site installation time bellow two weeks and improve the indoor environmental quality. At the same moment, the project aimed on implementation of systemic quality control over the whole design, pre-production, production and installation process in order to significantly reduce the number of warranty claims by the clients. The paper describes the design process of the modular retrofitting system and a pilot installation made on a mock-up building to test the concept, and presents the experience made.